2019
DOI: 10.1111/codi.14740
|View full text |Cite
|
Sign up to set email alerts
|

Does intra‐operative flexible endoscopy reduce anastomotic complications following left‐sided colonic resections? A systematic review and meta‐analysis

Abstract: Aim Postoperative anastomotic leakage (AL) or bleeding (AB) significantly impacts on patient outcome following colorectal resection. To minimize such complications, surgeons can utilize different techniques perioperatively to assess anastomotic integrity. We aim to assess published anastomotic complication rates following left‐sided colonic resection, comparing the use of intra‐operative flexible endoscopy (FE) against conventional tests used to assess anastomotic integrity. Methods PubMed/MEDLINE and Embase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that IOFS can identify immediate bleeding from an anastomosis 6,12 and that leads to a significant reduction in AB rates 10 . Our study, incorporating pooled data from our included studies, shows that IOFS is associated with a statistically significant reduction in the incidence AB requiring intervention.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have shown that IOFS can identify immediate bleeding from an anastomosis 6,12 and that leads to a significant reduction in AB rates 10 . Our study, incorporating pooled data from our included studies, shows that IOFS is associated with a statistically significant reduction in the incidence AB requiring intervention.…”
Section: Discussionsupporting
confidence: 57%
“…Our systematic review and meta‐analysis builds on the findings of Aly et al 10 . by including Shibuya et al ., 20 having been published subsequently, and Li et al 17 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In these two cases, a protective loop ileostomy had been performed in primary procedure. The risk for anastomotic leakage differs in the literature between 7 and 30% [28][29][30]. To reduce the anastomotic leakage rate, we introduced intraoperative flexible endoscopy for air leak testing immediately after stapling of the anastomosis during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…In these two cases a protective loop ileostomy had been performed in primary procedure. The risk for anastomotic leakage differs in literature between 7-30% [28][29][30]. To reduce the anastomotic leakage rate, we introduced intraoperative exible endoscopy for air leak testing immediately after stapling of the anastomosis during the study period.…”
Section: Discussionmentioning
confidence: 99%